Student Experience And Compliance With Actions Of Learning From Home During Covid 19 In NTT - Sidarta SAGITA; Maria Agnes E. DEDY; I Made ARTAWAN (International Journal of Environmental, Sustainability, and Social Science, 2022)
On August 6, 2021, the State of NTT confirmed that 41,539 people tested positive for Corona and 790 people died. As one of the states most affected by COVID-19. Transmission of COVID-19 can be prevented through knowledge and attitudes, which influence appropriate preventive actions in communities. One of them is a health student. Health students, especially students, are actively participating in current health trends as they are at the forefront of future healthcare facilities. This study aims to apply the health protocols that have been established. First, most students maintain physical distancing or keep their distance when leaving the house or doing activities in crowds. This study used an analytical observational research method with a cross-sectional approach and a qualitative method with random interviews. Based on the results of the survey and discussion above, 86.9% of Nusa Cendana University students are motivated by good knowledge about COVID-19. 90.6% of students at Nusa Cendana University are motivated by their positive attitude towards COVID-19. 90.0% of Nusa Cendana University students are motivated to take preventive measures against COVID-19. Based on the conclusion, there is a significant one-way relationship between knowledge and behavior of preventing COVID-19 in online learning methods with sufficient correlation strength (p<0.05 and r=0.415) in Nusa Cendana University students. There is a significant one-way relationship between attitudes and behavior to prevent COVID-19 in online learning methods with sufficient correlation strength (p<0.05 and r=0.450) in Nusa Cendana University students.